Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kecerdasan Emosional dan Hasil Belajar Siswa Pada Mata Pelajaran Fiqh di Madrasah Tsanawiyah Kecamatan Sakra Barat Tahun Pelajaran 2023/2024 - Muhtar, Muhamad Alwi; Lubna, Lubna; Efendi, M. Harja (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aims to evaluate the influence of Problem Based Learning (PBL) model on students' emotional intelligence and learning outcomes in the subject of Fiqh at Madrasah Tsanawiyah in the Sakra Barat Subdistrict for the academic year 2023/2024. A quantitative research method was employed with a pretest-posttest control group design experiment. Data collection was conducted through emotional intelligence tests and Fiqh learning outcome tests. Data analysis involved comparing the mean pretest-posttest differences between the control and experimental groups using independent t-tests. The results indicate that the implementation of PBL significantly enhances students' emotional intelligence and learning outcomes compared to conventional methods. The implication of this study underscores the importance of considering appropriate teaching models to improve not only cognitive but also emotional intelligence aspects in Fiqh education. PBL can serve as an effective alternative in achieving these goals at Madrasah Tsanawiyah, providing a deeper understanding of the subject matter and fostering social and emotional skills necessary for daily life and religious practice.